2020
DOI: 10.1038/s41467-020-18167-4
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Cav1.2-mediated signaling is a pathway for ketamine-induced pathology

Abstract: The general anesthetic ketamine has been repurposed by physicians as an anti-depressant and by the public as a recreational drug. However, ketamine use can cause extensive pathological changes, including ketamine cystitis. The mechanisms of ketamine's antidepressant and adverse effects remain poorly understood. Here we present evidence that ketamine is an effective L-type Ca 2+ channel (Cav1.2) antagonist that directly inhibits calcium influx and smooth muscle contractility, leading to voiding dysfunction. Ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(78 citation statements)
references
References 64 publications
(74 reference statements)
6
72
0
Order By: Relevance
“…CMG was performed with PBS infusion (25 μL/min) as previously described. 32,33 Mice were anesthetized by a F I G U R E 1 AUR mouse model. A, Schematic diagram of AUR mouse model with the application of 50 or 80 cm water pressure.…”
Section: Cystometrogram (Cmg)mentioning
confidence: 99%
See 1 more Smart Citation
“…CMG was performed with PBS infusion (25 μL/min) as previously described. 32,33 Mice were anesthetized by a F I G U R E 1 AUR mouse model. A, Schematic diagram of AUR mouse model with the application of 50 or 80 cm water pressure.…”
Section: Cystometrogram (Cmg)mentioning
confidence: 99%
“…BSM strip EFS was carried out with a Grass S48 field stimulator (Grass Technologies, RI, USA) using standard protocols previously described. 32,33 EFS stimulation parameters were set as follows: voltage 50 V; duration: 0.05 ms; trains of stimuli: 3 s per single train; frequencies: 1, 2, 5, 10, 20, and 50 Hz.…”
Section: Electrical Field Stimulation (Efs)mentioning
confidence: 99%
“…In cultured smooth muscle cells (SMCs), ketamine induces dose‐dependent inhibitory effects on cell generation 19,20,224 . Among the MAPK family, ERK1/2 is one of the well‐known signal transduction pathways for SMC differentiation and proliferation.…”
Section: Bsm Abnormalitiesmentioning
confidence: 99%
“…A previous study found that ketamine suppressed signaling pathways mediated by muscarinic receptors heterologously expressed in Xenopus oocytes, 233 which partially explained the mechanism of the inhibition of smooth muscle contraction in response to cholinergic stimulation with ketamine. However, we recently reported that ketamine and its metabolite nor‐ketamine could dose‐dependently inhibit BSM contraction in response to electrical field stimulation (EFS), high K, carbachol, and α, β‐meATP 20 . Purinergic and cholinergic signaling and high K levels all stimulate smooth muscle contraction by initiating an increase in the intracellular calcium concentration.…”
Section: Bsm Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation